Investigating the fundamentals of drug crystal growth using Atomic Force Microscopy - Thompson, Claire (2003)
The importance of crystals to the pharmaceutical industry is evident - over 90% of pharmaceutical products contain a drug in crystalline form. However, the crystallization phenomena of drug compounds are poorly understood. An increased understanding of these processes may allow a greater degree of control over the crystallization outcomes, such as morphology, purity, or stability. In these studies, we have applied Atomic Force Microscopy (AFM) to the in situ investigations of drug crystal growth.